Peculiarities Of Interaction of the Banking System with the Real Sector of the Economy (Eurasian Journal of History, Geography and Economics, 2022)
In this scientific and theoretical article ione of the stages of the author’s dissertation research in the field of integration and interaction of the banking system with the real sector of the economy is revealed. In modern economic and political realities in the world and domestic capital market, processes related to integration and interaction play an important role in stable mutually beneficial evolutionary development and financial security.